2017
DOI: 10.1002/ajcp.12203
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment, Problem Behaviors, and Neighborhood Attainment

Abstract: Using data from a prospective cohort design study of a group of children with documented histories of abuse and neglect (n = 908) and matched controls (n = 667), this paper examines whether problem behaviors (e.g., prostitution, crime, school problems, and homelessness) in young adulthood explain the link between maltreatment in childhood and living in high-risk neighborhoods in middle adulthood. Problem behaviors were assessed at mean age of 29 and neighborhood characteristics were assessed at mean age of 40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Parental history of being maltreated as a child increases the chances that offspring will be the subject of a child maltreatment report (Bartlett, Kotake, Fauth, & Easterbrooks, 2016; Berlin, Appleyard, & Dodge, 2011), but the role of neighborhoods in this transmission has not typically been evaluated. However, a follow-up study of adults who were maltreated in childhood showed them to be at higher risk than matched controls of living in distressed neighborhoods (Chauhan, Schuck, & Widom, 2017). It would be important for future research to investigate whether maltreated parents’ adverse selection into disadvantaged neighborhoods accounts for some of the geographic patterns of child maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Parental history of being maltreated as a child increases the chances that offspring will be the subject of a child maltreatment report (Bartlett, Kotake, Fauth, & Easterbrooks, 2016; Berlin, Appleyard, & Dodge, 2011), but the role of neighborhoods in this transmission has not typically been evaluated. However, a follow-up study of adults who were maltreated in childhood showed them to be at higher risk than matched controls of living in distressed neighborhoods (Chauhan, Schuck, & Widom, 2017). It would be important for future research to investigate whether maltreated parents’ adverse selection into disadvantaged neighborhoods accounts for some of the geographic patterns of child maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…If individuals with histories of neglect focus their efforts on meeting basic needs, this may come at the expense of finishing high school, getting a college degree, or finding adequate employment. There is some support for this proposition in the research that has linked childhood maltreatment to lower levels of academic achievement, unstable employment, and residence in neighborhoods in adulthood with more economic disadvantage [35,36].…”
Section: Plos Onementioning
confidence: 98%
“…Future research needs to examine other explanations for these relationships. Lower levels of academic achievement [53] and economic productivity [2], elevated psychopathology [43,46,54], higher levels of crime [55] and risk behaviors among maltreated children in adolescence and young adulthood may put them at risk for residence in worse neighborhoods [8] and result in higher levels of lead in their homes and apartments. Prior research has found that adults with histories of childhood maltreatment are at higher risk for poor health outcomes [3,6,[56][57][58], including cardiovascular, endocrine and pulmonary systems, compared to demographically matched adults without such histories.…”
Section: Plos Onementioning
confidence: 99%
“…Child maltreatment represents a major public health problem in the United States and abroad, with lasting impacts on health, social, and economic functioning [2][3][4][5][6]. Childhood maltreatment has been linked to increased risk of living in neighborhoods with less desirable characteristics [7,8] and higher levels of economic disadvantage [9][10][11].…”
Section: Introductionmentioning
confidence: 99%